The Influence of Knowledge, Self-Motivation, and Family Support on Accuracy Number, Type, and Schedule of Meals in Outpatient Type II DM Patients - Teulela Saratni; Reni Sofiyatin; Ni Ketut Sri Sulendri; AASP Chandra Dewi (Poltekkes Kemenkes Mataram, 2024)
Background: According to Riskesdas data in 2018, the prevalence of Diabetes Mellitus in the population aged ≥15 years on the national average increased by 2% from 2013 (Kemenkes RI 2018). Eating arrangements are essential in the management of type II DM. Eating arrangements in type II DM patients follow the 3J principle: the right amount, type, and meal schedule. Several factors influence dietary compliance, including the patient's knowledge related to the disease, namely DM, self-motivation from within the patient, and support from the patient's family. Based on the background, the researcher is interested in conducting research -on the influence of knowledge, self-motivation, and family support on the accuracy of the amount, type, and schedule of meals in outpatient type II DM patients at Pagesangan Health Center‖. Research Methods: The study was quantitative. The research subjects were 22 people. Questionnaires were used to measure knowledge, self-motivation, and family support. In addition, the 24-hour Recall Form is used to measure the accuracy of the amount, type, and meal schedule. The analysis used was a Chi-Square analysis test to determine the effect of the variables studied. Research Result: There is no effect of knowledge, self-motivation, and family support on the accuracy of the amount of food, type of food, and meal schedule in type II DM patients at Pagesangan Health Center. Conclusion: There is no effect of knowledge, self-motivation, and family support on the accuracy of the amount of food, type of food, and meal schedule in type II DM patients at Pagesangan Health Center.